Digestibilidade aparente do concentrado proteico de soja e glúten de milho pela tilápia do Nilo - Nettson, Luciana Valéria (2019)
This work evaluated the effect of inclusion levels of soy protein concentrate (CPS) and corn gluten (GM) on the apparent digestibility coefficient (CDA) of crude protein (CP) and crude energy (EB) of these ingredients by the Nile tilapia. The experiment was conducted in the aquaculture laboratory of GEMAq – Unioeste (Western Parana State University), in two stages, with duration of 21 days for CPS and 21 days for GM. We used 480 specimens of tilapia with a mean weight of 443 g, distributed in 24 tanks of 500L adapted for fecal collection, in a completely randomized design with six treatments (one reference diet and five diets with inclusion levels of 6, 12, 18, 24 and 30%) and four replicates. The values obtained from CDA PB and CDA EB from CPS and GM did not differ significantly between the inclusion levels of the ingredients evaluated in the present work. The inclusion levels of CPS and GM in Nile tilapia diets evaluated in this work do not interfere with the apparent digestibility coefficients of the protein and energy, and levels from 6 to 30% can be used in rations for specimens of this group with an average weight of 443g, without effects on the digestibility of these ingredients.